2018
DOI: 10.5588/ijtld.17.0802
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of line-probe assay for molecular analysis and drug susceptibility of extra-pulmonary tuberculosis

Abstract: Given the paucibacillary nature of EPTB, we demonstrated that PCR and LPA can have a vital role in establishing TB diagnosis in extra-pulmonary tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Although NTM has been reported as an important pathogen in PTB samples, musculoskeletal infections with NTM are rarely reported, but our laboratory is sensitized to NTM diagnosis in EPTB samples, and a similar finding has been reported in EPTB samples in one of our previous studies, too [ 4 , 14 , 15 ]. Thus, it is imperative that the possibility of NTM in MSTB samples needs to be explored and all possible measures taken to identify this pathogen at all laboratories.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although NTM has been reported as an important pathogen in PTB samples, musculoskeletal infections with NTM are rarely reported, but our laboratory is sensitized to NTM diagnosis in EPTB samples, and a similar finding has been reported in EPTB samples in one of our previous studies, too [ 4 , 14 , 15 ]. Thus, it is imperative that the possibility of NTM in MSTB samples needs to be explored and all possible measures taken to identify this pathogen at all laboratories.…”
Section: Discussionsupporting
confidence: 81%
“…India, with a large pool of mono-resistant along with rising multidrug-resistant TB (MDR-TB) patients, needs an active approach to tackle the problem. In 2015, India reported 20,763 patients with MDR-TB [ 4 ]. The rise was exponential in 2016 with 3.9% of new and 21% of previously treated cases being MDR.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has indicated that the incidence and prevalence of extrapulmonary tuberculosis may be underestimated due to several factors, including inadequate attention to extrapulmonary tuberculosis, insufficient diagnostic methods, and low rates of confirmation. This situation has led to a consistently lower cure rate for EPTB compared to PTB, posing challenges to global tuberculosis control efforts (Gambhir et al, 2017;Raghuvanshi et al, 2018). In this study, the detection rates of Gene Xpert, TB-DNA, and sputum culture for extrapulmonary tuberculosis are as follows: 11.76%, 16.67%, and 25%.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast to these molecular methods, the conventional AFB microscopy showed the lowest-yielding performance for the detection of EPTB cases with a sensitivity of 27.0% and 25.3% against culture and CRS, respectively, whereas the specificity was 99.1% and 100%, respectively. This poor sensitivity of AFB microscopy, however, is not surprising, as former studies have already described the lower sensitivity of this model [28,29]. The specificity of AFB microscopy (99.1%) is higher in terms of culture compared to the Xpert MTB/RIF (96%) and MTBDRplus assay (96.5%).…”
Section: Discussionmentioning
confidence: 58%